In Vitro Antibacterial, Antioxidant, Cytotoxicity Activity, and In Silico Molecular Modelling of Compounds Isolated from Roots of Hydnora johannis - Teshome Degfie; Milkyas Endale; Muhdin Aliye; Rajalakshmanan Eswaramoorthy; Tariku Nefo Duke; Aman Dekebo (Biochemistry Research International)
The plant Hydnora johannis has been utilized in folk medicine. Analyzing phytochemical composition of dichloromethane/methanol (1 : 1) root part of Hydnora johannis gave oleic acid (1), caffeic acid-2-hydroxynonylester (2), catechin (3), and a pregnane derivative (4). NMR spectroscopy was used to characterize compounds 1–3, while compound 4 was identified through GC-MS analysis and literature comparison. The cytotoxicity of extracts from roots of H. johannis was conducted against MCF-7 cell lines (human breast cancer) by MTT assay. According to the cytotoxicity study, n-hexane extract exhibited a high level of toxicity with 28.9 ± 5.6% cell viability. Antibacterial activity was tested against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus pyogen. The highest bacterial growth mean inhibition zone was measured for catechin (3) (13.72 ± 0.05 mm)) against P. aeruginosa at 0.25 mg/mL and acceptable related to standard. Antioxidant activity was studied by the DPPH assay. Based on the data from the antioxidant study, DCM/MeOH extract (70.32%) and catechin (3) showed good antioxidant activity (65.61%) (IC50 0.25 μg/mL) relative to that of the positive control (78.21%, IC50 0.014 μg/mL) at 12.5 μg/mL. In each docking pose, catechin (3) scored higher binding affinity of −7.9, −7.2, and −6.4 kcal/mol towards PqsA, DNA gyraseB, and S. aureus PK, respectively, compared to amoxicillin (−8.1, −6.1, and −6.4 kcal/mol). All five Lipinski rules were obeyed by compounds 1–3, which showed an acceptable drug resemblance. The lipophilicity was computed as less than five (1.47–4.01) indicating a lipophilic property. Catechin (3) obeys Veber’s rule implying its good oral bioavailability. Binding affinity scores of catechin (3)-protein interactions are in line with those from in vitro tests, indicating its potential antibacterial effect. The obtained cytotoxicity and antibacterial activity results support the utilization of H. johannis in folk medicine.